Studi Kelayakan Outer Ring Road Semarang Tahun 2009 Sebagai Alternatif Penentuan Kebijakan PemDA - CAROLINE CAROLINE (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2010)
Each Organization public sector or private have a goals. Strategy need reach a goal oforganization. It is describe at activities. Organization need reins management system forguarantee to do of strategy organization effective and efficient system. The system forguarantee to do of strategy organization is decision maker at government region. The exampleis Outer ring road Semarang. Semarang have strategy position for national road, Outer ringroad Semarang. Semarang have strategy position for national road, Outer ring road Semarang.Semarang has a strategy position for national road, province road, regency road and city road.In order to do need strategy management coordination each regent. Central Government haveplan build ring road Semarang-Solo need supported Government Semarang. The Conclusionis, first alternative Trase (Gunung Pati street, Cangkiran, Kalimas, Mangkang) have highfeasibility views. First alternative have some problem. Problem solving need a good branchof road, consistency middle ring road plan at BSB (Bukit Semarang Baru Regency). Secondalternative (Pramuka Street, New street, Kalimas and Mangkang) have feasibility stage two.Second alternative needs progress anticipate for conservation region plan, middle ring roadplan, space regulation specific for growth ple, intensive socialization society.Keywords : Management Strategic, Visibility Study, Outer Ring Road Semarang, Analysis Financial